CO2-free production of hydrogen via pyrolysis of natural gas: influence of non-methane hydrocarbons on product composition, methane conversion, hydrogen yield, and carbon capture - Ahmet Çelik; Iadh Ben Othman; Heinz Müller; Olaf Deutschmann; Patrick Lott (Discover Chemical Engineering)
Abstract Methane pyrolysis represents a CO2-free hydrogen production route that enables simultaneous carbon capture. While the majority of previous studies in the field focus on pure CH4 as feed gas stream, commercial processes will typically rely on natural gas as feedstock that contains also non-methane hydrocarbons such as ethane, propane, and n-butane. Therefore, the present study evaluates how CH4 conversion, H2 selectivity, product composition, and solid carbon yield evolve when using either pure CH4 or synthetic natural gas (SNG) as feed gas stream for a thermal pyrolysis process in a lab-scale high-temperature reactor. For this, industrially viable conditions are applied, namely temperatures between 1000 °C and 1600 °C, residence times between 1 s and 7 s, and molar H2 dilution ratios between 1:1 and 4:1. Although the use of SNG results in slightly lower hydrocarbon conversions because the additional components in SNG result in a higher effective H2 dilution ratio compared to a CH4-only feed, the non-methane hydrocarbons in the SNG have a positive effect on both H2 selectivity and solid carbon yield. Taking existing mechanistic understanding into account, these positive effects are attributed to radicals formed from the non-methane hydrocarbons, which facilitate dehydrogenation steps from ethane to ethylene and hereby increase the relative amount of H2 originating from CH4. The introduction of a carbonaceous fixed bed further benefits the performance of the pyrolysis process and ultimately enables to capture more than 98% of carbon in its solid form under industrially viable process conditions.